MENGARUNGI GARIS WALLACE: Awal Migrasi Manusia dari Paparan Sunda menuju Kawasan Wallacea - Sofwan Noerwidi (Berkala Arkeologi, 2008)
Human migration in prehistoric times strongly suggest very complex problems, which could be explained from various perspectives. This article attempts to explain fundamental aspect influencing the pattern of human migration in prehistoric times from Sunda Continent to Wallacean Zone. These aspects are, for example, environment, technology, culture and human being as a decision maker. Reconstructing interisland migration pattern of homo sapiens of hunter gatherer is not as easy as imagining interisland closest lines. This is because the focus of modern human migration is to search for a new area for exploiting natural resources.